O ofício de cabo eleitoral : entre campanhas, comícios e o dia a dia da política - Santos, Pâmella Synthia Santana (2016)
This dissertation has the intention in analyze how is “fabricated” a canvasser and how abilities of the politics office are seized and incorporated. Within that, the central empirical object are the canvassers that act as city councilmen of the fictitious city of Arapongas and they represent a case where can be discussed the relationship shown above. The dynamic of this county is favorable for a further analisys of the canvasser because it is a local that there are two political groups ruling the political daily. To comprehend the canvasser in general, a survey of what was already being discussed about him was necessary and the need of works that focus this actor became perceptible, even so, it was possible based on readings passing through the Sociology of Professional Groups as those which are inserted in a line of the Symbolic Interacionism and also passes through Political Sociology. We also rely on works of the Anthropology of Politic and also of the Politic Science. The second step happened to have na idea in how the political profession was beind developed, noting the historical and political contexto of the county of Arapongas and its relationship with the State. In the third part, an analysis of the daily politics was made in order to get to know this political actor when he is in its “habitat”. In the last part, we propose to face the canvasser as an occupation that has its own license and mandate, from the raised configuration of their background. The result of this so marginalized acting inside the own politics has shown that being a canvasser requires an “expert knowledge” of a specific skill to the fulfillment of this “new” profession.